Experimental Determination of Parameters of Nonlinear Electrical Load - Aleksandr Skamyin (MDPI AG, 2021)
The paper deals with issues of modeling nonlinear electrical loads of various types, such an uncontrolled rectifier, thyristor rectifier, thyristor power regulator and mixed equivalent nonlinear load. For these load types, existing analytical expressions were identified to determine the magnitudes of harmonic currents, and waveforms of currents were obtained during measurements in laboratory conditions with variable parameters of the grid impedance and load. The obtained results were compared, and it was found that the error in determining the magnitudes of harmonic currents can reach 60% for an individual load and 54% for an equivalent load. A more accurate method for determining the parameters of nonlinear electrical load is also proposed, which is based on the application of shunt harmonic filters. In laboratory conditions, it was found that when using the developed method, the error did not exceed 10% for an individual load and 14% for an equivalent load.